Priority Directions for Tourism Development in Uzbekistan - Hamid Turaev; Ian Patterson (Indonesian Journal of Law and Economics Review, 2020)
The tourism sector is becoming one of the most important strategic sectors of Uzbekistan. Presently, reforms are underway to develop strategies to solve many of the important social and economic issues such as job creation, expand the economy and hasten the development of the regional areas, as well as increasing earnings and quality of life of the country’s population. The main priorities of the state government policy in the field of tourism includes supporting its status as a strategic sector of the economy, and as a powerful tool for sustainable development. Between 2018-2019 this strategy is a logical continuation of state policy. This has been pursued by the country’s management and is aimed at maximizing the creation of an environment that includes economic, administrative and legal aspects which will contribute to the accelerated development of the tourism industry in Uzbekistan. Furthermore, this also includes expanding the economic potential of the regions and their revenue base, creating new jobs, increasing the number of tourists arriving in the republic, as well as actively promoting the national tourist product to world markets